ANALISIS PERILAKU MANAJEMEN KEUANGAN MAHASISWA FAKULTAS EKONOMI UPN VETERAN JAKARTA DIMASA PANDEMI COVID-19 - Nuroeni Qalbu Waty (2021)
This research includes quantitative research aimed at finding out each of the influences of financial literacy variables, parental income, hedonistic lifestyle on financial management behavior. The population in this study is a student of the faculty of economics UPN "Veteran" Jakarta. The sample in this study amounted to 100 respondents, with probability sampling method. The data was collected by distributing the quesionnaire. The analysis technique used is the Partial Least Square (PLS) analysis method. The results of this study show that: (1) Financial literacy has no significant effect on student financial management behavior during the covid-19 pandemic, (2) Parents' income has a significant influence on student financial management behavior during the covid-19 pandemic, (3) Hedonist lifestyles have a significant effect on student financial management behavior during the covid-19 pandemic.